Empowering SME Success: Unraveling the Nexus of Knowledge-Oriented Top Management, Knowledge-Sharing Practices, and Open Innovation on Performance - Tahmasebinia, Zhenia; Mohebi, Amir; Fardmehrgan, Sogand (Business and Economic Research, 2023)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">This study investigates the correlation between Knowledge-oriented top management, Inward and outward knowledge-sharing practices, and the impact they have on Inbound open innovation and business performance. Leadership is acknowledged as a crucial factor in effectively managing an organization, particularly in relation to knowledge management success. Our focus is on knowledge-oriented leaders' perspectives on knowledge sharing strategies and practices, and their pivotal role in establishing and implementing open innovation in small and medium-sized enterprises (SMEs). Such practices contribute to long-term success by reducing costs, expediting time to market, enhancing market differentiation, and creating new revenue streams for SMEs. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">To test our theoretical model, we utilized SMARTPLS version 4 and collected data from a sample of 247 IT, marketing, and sales managers in Tehran, the capital of Iran. The results indicate that knowledge-oriented top management has a positive and significant influence on both inward and outward knowledge-sharing strategies and practices, inbound open innovation, and ultimately, business performance. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Hence, the top manager and chief executive officer of a company, as role models with higher positions and authority, play a pivotal role in mobilizing the tangible and intangible resources of the company. They can establish a conducive culture, foundation, and incentives for sharing valuable and relevant knowledge across the organization and departments. This, in turn, fosters creativity, innovation, and departmental outputs, ultimately leading to improved overall business performance for the firm.